Baghdadi Jewish networks in the age of nationalism - Goldstein-Sabbah, S. R. (Brill's series in Jewish studies, 2021)
"Baghdadi Jewish Networks in the Age of Nationalism traces the participation of Baghdadi Jews in Jewish transnational networks from the mid-nineteenth century until the mass exodus of Jews from Iraq between 1948 and 1951. Each chapter explores different components of how Jews in Iraq participated in global Jewish civil society through the modernization of communal leadership, Baghdadi satellite communities, transnational Jewish philanthropy and secular Jewish education. The final chapter presents three case studies that demonstrate the interconnectivity between different iterations of transnational Jewish networks. This work offers a corrective to the recent trend of studying Iraqi Jews through their engagement with Arab/Iraqi Nationalism or Zionism/anti-Zionism, by exploring Baghdadi participation within transnational Jewish networks"